The Influence of Kampus Mengajar Program in Forming Pedagogical Competence of Undergraduate English Education Students - Riksandi Ihza Nugraha; Zacky Muhtar Afandi; Dellima Nuriyanwar; Hana Azzahra; Lystiana Nurhayat Hakim, (Journal of Applied Linguistics (ALTICS), 2025)
Undergraduate students today have greater opportunities to gain practical experience in professional settings through ‘Merdeka Belajar Kampus Merdeka’ (MBKM) programs, one of which is Kampus Mengajar. This study aims to determine the extent to which participating in the Kampus Mengajar program influences the pedagogic competence of undergraduate English education students. This study uses a quantitative survey approach with a cross-sectional design. A questionnaire consisting of 20 items was used as the research instrument. Employing the snowball sampling technique, this study obtained 60 participants from 20 universities across Indonesia who met the population criteria. To analyze and describe the data, this study used SPSS version 25. The findings show that there is a significant influence from participation in Kampus Mengajar in forming pedagogic competence, as demonstrated by a mean score of 83.38 out of a maximum of 100. The results also suggest that the ability to manage a safe and comfortable learning environment, with an average score of 25.37 out of 30 at maximum, is the most significantly impacted aspect of pedagogic competence influenced by participation in Kampus Mengajar. Further research is necessary to explore other dimensions of pedagogic competence and to verify these findings with larger and more diverse samples.